1998
DOI: 10.1557/proc-518-131
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Polysilicon Microbeams in Controlled Humidity Ambients

Abstract: controlled humidity ambients. Beams were freed by supercritical C02 drying. Consistent adhesion results were obtained using a post-treatment in an oxygen plasma which rendered the microbeams uniformly hydrophilic. Individual beam deformations were measured by optical interferometry after equilibration at a given relative humidity (RH). Validation of each adhesion measurement was accomplished by comparing the deformations with elasticity theory. The data indicates that adhesion increases exponentially with RH f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 12 publications
0
34
1
Order By: Relevance
“…However, even at 90% and greater RH, this was not observed -crack lengths decreased only= a result of a pad actuation cycle. This is in striking contrast to the case of hydrophilic beams, where we observed spontaneously decreasing crack lengths with increasing humidity over a range from 30 to 95% RH [36]. In that case, nanometer size capillaries at the crack tip do work against the strain energy of the beam to heal the crack.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…However, even at 90% and greater RH, this was not observed -crack lengths decreased only= a result of a pad actuation cycle. This is in striking contrast to the case of hydrophilic beams, where we observed spontaneously decreasing crack lengths with increasing humidity over a range from 30 to 95% RH [36]. In that case, nanometer size capillaries at the crack tip do work against the strain energy of the beam to heal the crack.…”
Section: Discussioncontrasting
confidence: 83%
“…Although a drying front of water moving across the surface was observed in one video frame and had disappeared in the next (30 msec later) due to its rapid velocity over the hydrophobic surface, water remained microscopically in the vicinity of the beams for a full second, and clearly pulled the beams fiu-therin. ODTS density on the substrate surface is known to be a strong function of deposition conditions [36]. We hypothesize that because the ODTS fdm did not attain maximum density in our deposition, the adhesion-controlling receding contact angle 6'Cr was less than 90°.…”
Section: Ldrd Funabmental Mechanisms Of Micromachine Reliabili~ Sandmentioning
confidence: 90%
“…This treatment results in beam and substrate surfaces that are covered by a thin layer of hydrophilic SiO2. In a previous report [37], we showed that the adhesion energy for silica covered surfaces is dominated by the inherent roughness of the poly silicon. For perfectly smooth, wetted surfaces one predicts and measures [38] an adhesion energy that is twice the surface energy of water (ywate.= 73 mJ/m2), or about 146 mJ/m2.…”
Section: ) Are the Values For Adhesion Between S-shaped And Arc-shapmentioning
confidence: 75%
“…This method gives great latitude in measuring adhesion because equilibrium is deep and easily attainable from either side of the equilibrium. Studies such as the effect of environment on adhesion are readily adapted to this method [37]. Adhesion values are relatively insensitive to local statistical variations in the surface topography.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, de Boer [80] has shown that the adhesion between a polysilicon beam and the polysilicon surface increased exponentially between 30 to 90% RH.…”
Section: Dormancymentioning
confidence: 99%